Cri-du-chat syndrome mimics Silver-Russell syndrome depending on the size of the deletion: a case report - Yerai Vado; Javier Errea-Dorronsoro; Isabel Llano-Rivas; Nerea Gorria; Arrate Pereda; Blanca Gener; Laura Garcia-Naveda; Guiomar Perez de Nanclares (BMC Medical Genomics, 2018)
Abstract Background Silver-Russell Syndrome (SRS) is a rare growth-related genetic disorder mainly characterized by prenatal and postnatal growth failure. Although molecular causes are not clear in all cases, the most common mechanisms involved in SRS are loss of methylation on chromosome 11p15 (≈50%) and maternal uniparental disomy for chromosome 7 (upd(7)mat) (≈10%). Case presentation We present a girl with clinical suspicion of SRS (intrauterine and postnatal growth retardation, prominent forehead, triangular face, mild psychomotor delay, transient neonatal hypoglycemia, mild hypotonia and single umbilical artery). Methylation and copy number variations at chromosomes 11 and 7 were studied by methylation-specific multiplex ligation-dependent probe amplification and as no alterations were found, molecular karyotyping was performed. A deletion at 5p15.33p15.2 was identified (arr[GRCh37] 5p15.33p15.2(25942–11644643)× 1), similar to those found in patients with Cri-du-chat Syndrome (CdCS). CdCS is a genetic disease resulting from a deletion of variable size occurring on the short arm of chromosome 5 (5p-), whose main feature is a high-pitched mewing cry in infancy, accompanied by multiple congenital anomalies, intellectual disability, microcephaly and facial dysmorphism. Conclusions The absence of some CdCS features in the current patient could be due to the fact that in her case the critical regions responsible do not lie within the identified deletion. In fact, a literature review revealed a high degree of concordance between the clinical manifestations of the two syndromes.